2018
DOI: 10.5539/gjhs.v10n8p41
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Cognitive Factors Associated With Condom Use, Multiple Sexual Partnerships, and Contraception Use Among Sexually-Active Adolescent Girls in Uganda

Abstract: Many adolescent girls start sexual activity early which exposes them to health risks of HIV and unplanned pregnancies. However, adolescent girls are less likely than boys to initiate discussion or demand use of condoms. Multiple sexual partnerships among girls are reported to be on the rise with eminent transactional sex and pre-marital relationships. The unmet need for contraception among adolescent girls is also high. A cross-sectional survey covering 16 districts in Uganda assessed the socio-cognitive facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Although studies found that males are more likely to have multiple concurrent sexual partners than females, it is still unclear why adolescents with HIV are more likely to be female than male if MCSP increases the risk of contracting HIV (1, 38). It is also not yet clear why adolescents attending family planning clinics are eager to address their reproductive concerns, but appear to be less concerned about STDs (36, 37). This indicates an urgent need to discover why adolescents continue to risk contracting HIV through sexual activity.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although studies found that males are more likely to have multiple concurrent sexual partners than females, it is still unclear why adolescents with HIV are more likely to be female than male if MCSP increases the risk of contracting HIV (1, 38). It is also not yet clear why adolescents attending family planning clinics are eager to address their reproductive concerns, but appear to be less concerned about STDs (36, 37). This indicates an urgent need to discover why adolescents continue to risk contracting HIV through sexual activity.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of the risks of MCSP among adolescents and their influencers was found to be inadequate and often intertwined with myths and misconceptions (65). Although several studies on adolescent sexual behaviors found that knowledge is weakly associated with the performance of the actual behaviors (36, 65, 67), information services remain important in clearing misconceptions and addressing health concerns. Brainstorming sessions and the literature showed that adolescents have low levels of self-efficacy toward having one sexual partner, often associated with the perception that peers have multiple sexual partners (34, 38).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations